2008
DOI: 10.1177/1098611107313942
|View full text |Cite
|
Sign up to set email alerts
|

What Matters

Abstract: Public attitudes toward the police are often studied because of their relationship with citizens' support of the existing order. Much of the literature on the public's opinion of law enforcement personnel and organizations, however, does not provide police practitioners with a clear strategy to improve matters. The current study, based on interviews of Santa Ana, California residents, represents an attempt to assess the relative influence of individual characteristics, perceptions, and ecological conditions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 70 publications
1
18
0
1
Order By: Relevance
“…Responses range from low (1) to high (4) exposure. Negative contact with police contributes to worse assessments of police (Bridenball & Jesilow, 2008;Hinds, 2009). We include a measure of negative police contact in the prior year coded 1 if the respondent reported negative contact, and 0 if the contact was positive, or there was no police contact.…”
Section: Control Variablesmentioning
confidence: 99%
“…Responses range from low (1) to high (4) exposure. Negative contact with police contributes to worse assessments of police (Bridenball & Jesilow, 2008;Hinds, 2009). We include a measure of negative police contact in the prior year coded 1 if the respondent reported negative contact, and 0 if the contact was positive, or there was no police contact.…”
Section: Control Variablesmentioning
confidence: 99%
“…Another consistent finding is that race/ethnicity influences attitudes toward the police. While a few scholars have concluded that race/ethnicity is not a robust predictor of confidence in the police (Bridenball and Jesilow, 2008;Cao and Wu, 2019), numerous studies indicate that racial/ethnic minorities view the police less favorably than do Whites (Hollis and Jennings, 2018;Peck, 2015;Reisig and Parks, 2000). To provide a couple of examples, Graham et al (2020) found that racial/ethnic minorities were significantly more likely than Whites to worry about being the victim of police violence and Mourtgos and Adams (2020, p. 886) reported "that race and minority ethnicity appear to be the most substantial influences on citizen assessments of police use-of-force."…”
Section: Demographic Characteristics: Age Race/ethnicity Gender and S...mentioning
confidence: 99%
“…Beyond the consensus that young people and racial/ethnic minorities view the police more negatively than older adults and Whites, the impact of demographic characteristics on perceptions of the police is equivocal (Brown and Benedict, 2002). There are studies which indicate that gender does not affect attitudes toward the police (Bridenball and Jesilow, 2008;Vogel, 2011;Wu et al, 2009), that females view the police more favorably than do males (Gabbidon et al, 2011;McCluskey et al, 2008) and that males view the police more favorably than do females (Correia et al, 1996;Mourtgos and Adams, 2020). For instance, Lai and Zhao (2010) reported that gender did not significantly impact a composite measure of trust in the police which included concerns about the police use of tasers, Thompson and Lee (2004) found that the effects of gender on perceptions of police violence varied depending upon the situation in which violence was used, and Mourtgos and Adams (2020) reported that women were more likely than men to be critical of the police use of force.…”
Section: Demographic Characteristics: Age Race/ethnicity Gender and S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Police. Youths' attitudes towards police develop based on a number of factors, including personal experiences, passive observations, conversations with friends and family, and the media (Bridenball & Jesilow, 2008;Gallagher et al, 2001;Granot et al, 2021;Piccirillo et al, 2021;Warren, 2011). However, youth who have been arrested have personal police experience to draw from.…”
Section: Juvenile Justice Systemmentioning
confidence: 99%